Research on Deviation Analysis and Proportional Correction Method for Face Gear Tooth Turning - Ren Minghui; Wei Bingyang; Deng Xiaozhong; Han Zhengyang (Jixie chuandong)
Based on the mathematical model of gear turning cutters and face gears, a tooth surface deviation model for gear turning is established using gear shaping as the theoretical tooth surface. Using the incremental method, the influence of machining parameters such as offset distance, cutting depth, shaft intersection angle, and rolling ratio on tooth surface accuracy is analyzed, and a method for correcting the tooth surface deviation ratio of face gears is presented. The tooth surface deviation in gear turning is mainly concentrated at four vertex positions, and the tooth surface deviation is most sensitive to the correction of the roll ratio, but not to the offset amount. Using a three-parameter deviation sensitivity matrix, the proportional relation between the tooth surface deviation and machining parameters is determined. Through two trial cuts, the tooth surface deviation is corrected, and the feasibility of the proportional correction method is verified.